Synthesis of Nanoscale Tips Using Femtosecond Laser Radiation under Ambient Condition - Sivakumar, M (Springer, 2009)
We report a unique growth of platelet-shaped nanoscale tips of transparent dielectric using femtosecond laser radiation at MHz pulse repetition rate with nitrogen background gas flow under ambient condition. The tips grew with sharp nanoscale apex while their base and lengths are of the order of few hundred nanometers. In the absence of nitrogen, the irradiation leads to nanofibrous structure formation. The collision between the nitrogen gas atoms and the vapor species slows down plume expansion and lead to an increase of nanoparticles size. This prevents the fibrous structure formation and provides appropriate condition for nanoscale tips growth.